[(x2+25)-13].3=36
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
`x^2=3`
`=>x=\sqrt{3}\or\x=-\sqrt{3}`
`x^2=36`
`<=>x^2=(+-6)^2`
`<=>x=+-6`
`x^2=25`
`<=>x^2=(+-5)^2`
`<=>x=+-5`
`2x^2+(-20)=55`
`<=>2x^2-20=55`
`<=>2x^2=75`
`<=>x^2=75/2`
`<=>x=+-\sqrt{75/2}`
`2(x-1)^2+5^0=9`
`<=>2(x-1)^2+1=9`
`<=>2(x-1)^2=8`
`<=>(x-1)^2=4`
`<=>x-1=2\or\x-1=-2`
`<=>x=3\or\x=-1`
1).( 27,56 x 35 ) + ( 27,56 x 67 ) - ( 27,56 x 2)
= (964 + 1846,52) - 55,12
=2810,52 - 55,12
= 2755,4
2).( 4x 35 ) x ( 25 x 5 ) x 2
= ( 140 x 125 ) x2
= 17500 x 2
=35000
4). 3/10
5). 1188
6). 61/6
\(a,\left(-31\right).\left(x+7\right)=0\\ \Rightarrow x+7=0\\ \Rightarrow x=-7\\ b,\left(8-x\right).\left(x+13\right)=0\\ \Rightarrow\left[{}\begin{matrix}8-x=0\\x+13=0\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=8\\x=-13\end{matrix}\right.\\ c,\left(x^2-25\right)\left(3-x\right)=0\\ \Rightarrow\left(x-5\right)\left(x+5\right)\left(3-x\right)=0\\\Rightarrow \left[{}\begin{matrix}x-5=0\\x+5=0\\3-x=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=5\\x=-5\\x=3\end{matrix}\right.\\ d,\left(x-3\right)\left(x^2+4\right)=0\\ \Rightarrow\left[{}\begin{matrix}x-3=0\\x^2+4=0\end{matrix}\right.\\ \Rightarrow\left[{}\begin{matrix}x=3\\x^2=-4\left(loại\right)\end{matrix}\right.\\ \Rightarrow x=3\)
X2=3 x2=25
=> X=\(\pm\sqrt{3}\) => x=5
X2=36
=> x=6
2.(x-1)2+50= 9
2.(x-1)2+1= 9
2.(x-1)2= 8
(x-1)2 = 8/2
(x-1)2 = 4
(x-1)2 = (2)2
x-1=(\(\pm\)2)
TH1: x-1= 2 TH2: x-1=-2
x=2+1 x =(-2)+1
x= 3 x = -1
Vậy x\(\in\)\(\left\{3;1\right\}\)
a)|x-75|+3=15
|x-75|=12
\(\Rightarrow\orbr{\begin{cases}x-75=12\\x-75=-12\end{cases}\Rightarrow}\orbr{\begin{cases}x=87\\x=63\end{cases}}\)
b)\(\left[\left(x^2+25\right)-13\right].3=36\)
\(\left[\left(x^2+25\right)-13\right]=108\)
\(\left(x^2+25\right)=121\)
\(x^2=96\)
x ko TM
a) |x-75|+3=15
|x-75| =15-3
|x-75| = 12
|x| =12+75
|x| = 87
{(x^2+25)-13}.3=36 (x^2+25)-13 =36:3 (x^2+25)-13 =12 x^2+25 =12+13 x^2+25 = 25 x^2 =25-25 x^2 =0 x^2 =0^2 x =0